Efeitos da vibração, do plano de oscilação e de uma sessão de uso da haste vibratória sobre o controle postural de mulheres idosas - Crozara, Luciano Fernandes [UNESP] (2015)
Because of sensory and motor changes with aging, elderly people show a reduced ability to maintain or restore the balance during standing posture. The mechanical vibration has been identified as an additional or alternative method for training or rehabilitation in different populations, including elderly. There are various devices and protocols for the application of vibration and among them, the vibration produced by the vibratory pole is distinguished by lower frequency of vibration achieved and the pole passive behavior, which vibration is not produced by external force, but by muscle contraction. Although have been reported some positive effects of the use of vibration on strength parameters, power, muscle activation and flexibility of older, yet its effects have not been investigated on postural control of elderly. In addition, there are no studies that investigated the isolated effect (controlled) of a vibratory pole, and there is no scientific recommendations on which pole oscillation plane would be best suited to optimize the stimulus of vibration on postural control. Therefore, the aim of this study was to analyze the effects of vibration, oscillation plane and a single session of the vibratory pole use on postural control of elderly women. These study included 32 older women (68 ± 5 years old), physically active, residents of Marilia-SP community. The experimental procedures were performed on a force platform, with sampling frequency of 100 Hz, in four conditions for each type of pole (vibratory or rigid - control): quiet standing posture pre pole use, standing posture with pole oscillating in the anteroposterior (a-p) direction in the transverse plane, standing posture with pole oscillating in the a-p direction in the sagittal plane and quiet standing posture immediately after pole use. Each condition consisted of 3 trials, lasting 30 s each with an interval of 40 s between them. It was given a 20 minutes rest between ...